Case Law: A Review of Selected Pharmaceutical Patents in the UK Courts During 2020 - Sarah-Jane Crawford; Harry Melville O'Brien; James Alexander Stones (University of Huddersfield Press, 2021)
Patents lie at the interface between technology and law. This article provides a critical review of four high profile cases from 2020 in which patents relating to pharmaceuticals were litigated in the UK Courts. The selected cases in this review involved 'sufficiency', 'novelty', 'inventiveness', 'plausibility' and 'infringement issues. The first case is a dispute between Regeneron Pharmaceuticals and Kymab Ltd in relation to Regeneron's patent for a transgenic mouse platform. The second case relates to Pfizer's patent for their Prevnar®13 pneumococcal vaccine and the alleged infringement of this patent by Merck Sharp & Dohme. The third case concerns the validity of a patent belonging to Neurim Pharmaceuticals Ltd relating to a slow-release formulation of melatonin for treating primary insomnia. The final case is a dispute between FibroGen Inc. and Akebia Therapeutics concerning FibroGen's patents for hypoxia-inducible factor prolyl hydroxylase enzyme inhibitors ("HIF-PHIs") for use in treating anaemia. The article aims to focus on the technology behind the patents and to provide an insight into how science interacts with law in the context of patent enforcement and infringement.